Intercultural competence in instructors of English as a Foreign Language - Sabando Moreira, Maria Belen; Franco Catagua, Jennifer Stefania; Villafuerte-Holguin, Jhonny; Intriago, Eder (Technium Education and Humanities, 2024)
This study aims to determine the evolution of the intercultural competence of English language instructors in Manta-Ecuador. It uses the postmodern paradigm and the mixed educational research approach. The participants are 311 instructors working in elementary educational public institutions. The instruments used are open-ended interviews, a survey, and contextualized observation. The results characterize the participants' perceptions of their intercultural competence and contrast with the interviews and teaching practice observations. The findings show high and medium knowledge and intercultural competencies levels. They emphasize the complex, multifaceted nature of intercultural competence and the contribution of training and teaching practice for developing instructors' professional profiles. It concludes that Ecuadorian EFL instructors report a weakness in their intercultural competence, situation that requires pedagogical support.